Asas Keseimbangan dalam Perjanjian Penjualan Makanan Tanpa Mencantumkan Harga - Rayhan Adhi Pradana (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The practice of food businesses in tourist areas not listing prices on menus disturbs consumers by violating their right to clear information. This study examines the form of consumer deception under Law Number 8 of 1999 on Consumer Protection and its legal consequences. The results show that failure to list prices is not absolutely prohibited, but when unclear pricing leads to unreasonable charges, it constitutes misleading conduct prohibited by Article 10(a) and violates consumers’ right under Article 4(c). Business actors may face criminal and administrative sanctions, while consumers may pursue litigation or settlement through the Consumer Dispute Resolution Body (BPSK).